2013
DOI: 10.1002/phy2.7
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular volume regulation in heart failure with preserved ejection fraction

Abstract: Ejection Fraction (EF) has attained the recognition as indicator of global ventricular performance. Remarkably, precise historical origins promoting the apparent importance of EF are scant. During early utilization EF has been declared a gold standard for the evaluation of the heart as a pump. In contrast, during the last two decades, clinicians have developed a measure of doubt in the universal applicability of EF. This reluctance lead to the introduction of a new and prevalent syndrome in which heart failure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 22 publications
0
32
0
2
Order By: Relevance
“…Traditionally, the PV loop depends on the triad, preload (i.e., EDV), afterload (often interpreted as MAP, or ESP), and contractile state. The latter refers to intrinsic contractile properties of the heart muscle and is reflected by the maximum slope (Emax) of the elastance curve, which corresponds with the ratio of LV pressure over volume (11). This line shows an intercept (Vo) with the volume axis.…”
Section: The Pv Loop For the Ventriclementioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, the PV loop depends on the triad, preload (i.e., EDV), afterload (often interpreted as MAP, or ESP), and contractile state. The latter refers to intrinsic contractile properties of the heart muscle and is reflected by the maximum slope (Emax) of the elastance curve, which corresponds with the ratio of LV pressure over volume (11). This line shows an intercept (Vo) with the volume axis.…”
Section: The Pv Loop For the Ventriclementioning
confidence: 99%
“…This means that, while taking a linear approach, Vo varies along with Emax, depending on the particular region where Emax is determined (3). Also, Vo has no direct physiological meaning, because it just refers to an extrapolation of a linearized approach used to describe systolic elastance in a simplified manner (11). In the nonlinear model, Emax should simply be viewed as the tangent at any particular point under consideration along the full trajectory of ESP-ESV combinations, the so-called end-systolic PV relationship.…”
Section: The Pv Loop For the Ventriclementioning
confidence: 99%
“…Experimental studies with volume loading have shown that utilization of Starling’s law is effective in improving LV function in the short term 11,12. Some investigators have shown that the alternative Starling’s law, based on the relation of SV to end-systolic volume (ESV),13,14 is a better indicator of LV function in HF. This may be more effective in identifying the differences between HFpEF and HFrEF patient groups.…”
Section: Hemodynamic Parameters Governing Left Ventricular Function Imentioning
confidence: 99%
“…In contrast, diastolic pressures for both the LV and aorta are not significantly different. These one-sided differences contribute to the finding that E max tends to be higher in HFpEF and therefore can be regarded as a cofactor leading to the uncoupling of EF and k 14. A larger pulse pressure (PP) is found in the HFpEF group, which is the consequence of a lower arterial compliance; as C is inversely proportional to PP 4,5…”
Section: Interaction Of the Coupled Lv–as In Hfmentioning
confidence: 99%
“…Unlike STICH, Kerkhof3 looked at subjects with heart failure with preserved ejection fraction. Additionally, they excluded patients on β-blockers because of the effect on the ejection fraction - end-systolic volume (EF-ESV) relationship, whereas 86% of the STICH population was on β-blockers.…”
mentioning
confidence: 99%